Race of the century eaudiobook The battle to break the four-minute mile. - Bascomb, Neal (Scholastic Audio Books, 2022)
Highly acclaimed author Neal Bascomb brings his peerless research and fast-paced narrative style to a young adult adaptation ofone of his most successful adult books of all time, The Perfect Mile, an inspiring and moving story of three men racing to achievethe impossible — the perfect four-minute mile. There was a time when running the mile in four minutes was believed to be beyond the limits of human foot speed. In 1952, aftersuffering defeat at the Helsinki Olympics, three world-class runners each set out to break this barrier: Roger Bannister was ayoung English medical student who epitomized the ideal of the amateur; John Landy the privileged son of a genteel Australianfamily; and Wes Santee the swaggering American, a Kansas farm boy and natural athlete.Spanning three continents and defying the odds, these athletes' collective quest captivated the world. Neal Bascomb's bestsellingadult account adapted for young adults delivers a breathtaking story of unlikely heroes and leaves us with a lasting portrait of thetwilight years of the golden age of sport.